Pengaruh Kualitas Produk dan Gaya Hidup Terhadap Keputusan Pembelian Mobil Toyota Yaris - Dendy Irawan; Vina Meliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to explain the influence of product quality and lifestyle towards purchase decision of Toyota Yaris in partial and simultaneous. This research using quantitative approach. Where the amount of samples taken are 185 people using purposive sampling technique. The measurement used in the form of a questionnaire distributed through Google form. The analyzing technique is using validity test, reliability test, classic assumption test, and hypothesis test. The result of this research has shown us that: according to the partial result on product quality, that variable have significant influence to purchase decision with Tvalue (7,384) > Ttable (0,298), and according to the partial result, even when the lifestyle varibale does not have significant influence to purchase decision with Tvalue (0,255) > Ttable (0,799), and according to the simultaneous test result on product quality and lifestyle have together influence on purchase intention with Fvalue (13,314)